2009
DOI: 10.1080/00016480802441754
|View full text |Cite
|
Sign up to set email alerts
|

Expression of aquaporins, vasopressin type 2 receptor, and Na+-K+-Clcotransporters in the rat endolymphatic sac

Abstract: mRNAs and proteins of AQP1-4, AQP6-9, V(2)-R, NKCC1, and NKCC2 were expressed, but AQP5 was not expressed in the rat endolymphatic sac.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 21 publications
1
29
1
Order By: Relevance
“…This is partially due to the fact that expression of NKCC2 has been only recently found in extratubular cells. Indeed, NKCC2 is expressed in specialised neurons of the gastrointestinal tract or interneurons (Gavrikov et al 2006, Xue et al 2009, Zhu et al 2011 and in cells of the gastric, intestinal, endolymphatic sac and olfactory epithelia (Akiyama et al 2007, Nickell et al 2007, Nishimura et al 2009, Xue et al 2009, Zhu et al 2011. In fact, low levels of Slc12a1 mRNAs appear to be widely distributed in human tissues (Di Fulvio & Alvarez-Leefmans 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This is partially due to the fact that expression of NKCC2 has been only recently found in extratubular cells. Indeed, NKCC2 is expressed in specialised neurons of the gastrointestinal tract or interneurons (Gavrikov et al 2006, Xue et al 2009, Zhu et al 2011 and in cells of the gastric, intestinal, endolymphatic sac and olfactory epithelia (Akiyama et al 2007, Nickell et al 2007, Nishimura et al 2009, Xue et al 2009, Zhu et al 2011. In fact, low levels of Slc12a1 mRNAs appear to be widely distributed in human tissues (Di Fulvio & Alvarez-Leefmans 2009).…”
Section: Introductionmentioning
confidence: 99%
“…8 Recently, it has come to light that this mechanism has a crucial role not only in the kidney but also in the inner ear. In addition, the following evidence has accumulated to suggest that VP is closely associated with the formation of EH: (1) plasma levels of arginine VP are higher in patients with MD and may depend on the phase that the patient is in, [9][10][11] (2) acute and chronic application of arginine VP produces EH in guinea-pigs and rats, [12][13][14] (3) V2 receptor mRNA is expressed in rat and human inner ear, [15][16][17][18] and (4) expression of V2 receptor mRNA in the rat inner ear is downregulated by VP application. 19 Such accumulated evidence has led to the assumption that production of endolymph is controlled by VP-AQP2 system.…”
mentioning
confidence: 99%
“…NKCC-2 was originally known as a kidney-specific cotransporter expressed only on the apical membrane of the TAL (Knepper and Brooks 2001;Mutig et al 2007). Its expression has been reported recently in human and rat ES (Nishimura et al 2008;Kakigi et al 2009); however, its detailed localization has not been reported. The present immunostaining results with specific anti-NKCC-2 antibody indicate that NKCC-2 is localized in the apical membranes of ES epithelia, specifically in the same pattern as in mammalian renal TAL (Knepper and Brooks 2001).…”
Section: Discussionmentioning
confidence: 97%
“…NKCC-2 is typically recognized as a kidney-specific ion transporter and is expressed in the apical membrane of the thick ascending limb (TAL) loop of Henle, where it is responsible for the reabsorption of ?20% of filtered NaCl (Gamba et al 1994). Recently, the protein expression of NKCC-2 in human and rat ES has been reported by using IHC (Nishimura et al 2008;Kakigi et al 2009); however, detailed tissue or cellular localization has not been reported. This study has elucidated the NKCC-2 localization pattern in each part of the ES and the coexpression pattern with Na 1 /K 1 -ATPase by immunohistochemical assessment, which may provide beneficial information to understand the ES ion transport system.…”
Section: /2clmentioning
confidence: 99%